Unified theory of alpha, mu, and tau rhythms via eigenmodes of brain activity - El Zghir, Rawan Khalil; Gabay, Natasha C.; Robinson, P. A. (Frontiers in Computational Neuroscience, 2024)
A compact description of the frequency structure and topography of human alpha-band rhythms is obtained by use of the first four brain activity eigenmodes previously derived from corticothalamic neural field theory. Just two eigenmodes that overlap in frequency are found to reproduce the observed topography of the classical alpha rhythm for subjects with a single, occipitally concentrated alpha peak in their electroencephalograms. Alpha frequency splitting and relative amplitudes of double alpha peaks are explored analytically and numerically within this four-mode framework using eigenfunction expansion and perturbation methods. These effects are